Concept of Accountant Ethics Based on Javanese Cultural Values - Ulfah, Fitriah; Prabowo, Muhammad Aras; Aryani, Habsyah Fitri; Hidayadi, Taufik; Hanipa, Siti Danila (Mahameru Publisher, 2023)
This study aims to integrate the richness of Javanese cultural values with the accountant's code of ethics to increase the professionalism and compliance of accountants with the code of ethics. The research method used is a literature review using descriptive data analysis. The literature sources used are in the form of books, journals, and research results that are appropriate to the research topic. The results of the study reveal that nine Javanese cultural values have integrity for strengthening the accountant's code of ethics.These values include (1) Ojo Dumeh (not selfish), (2) Alon-alon asal kelakon (be wise and careful), (3) Bahasa Jawa Kromo Inggil (communicate politely and politely), (4) Ewuh-pakewuh (Shyness), (5) Unggah-ungguh (Be respectful and polite), (6) Eling lan waspodo (careful and alert), (7) Sungkan (respect), (8) Mangan ora mangan sing penting kumpul (Togetherness), and (9) Rukun agawe (be cooperative). These nine values can be an alternative in strengthening professionalism and compliance with the code of ethics for accountants, especially accountants with Javanese ethnic background.